2021
DOI: 10.4103/ijo.ijo_1644_21
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal vein occlusion secondary to varicella zoster retinal vasculitis in an immunocompetent individual during the COVID-19 pandemic - A case report

Abstract: We report the occurrence of unilateral central retinal vein occlusion (CRVO) in a young yoga enthusiast who presented amidst the COVID-19 pandemic. Subtle signs of uveitis when systemically investigated revealed a multitude of causes, but ocular fluid polymerase chain reaction was positive for varicella zoster virus (VZV). The prompt initiation of antivirals resulted in a good visual outcome. Our case describes the rare presentation of VZV retinal vasculitis as CRVO in a young healthy individual and highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…CNS arteritis has been mentioned above. Retinal vasculitis is a severe, but rare complication of HZO treated by antiviral medication [62].…”
Section: Vasculitismentioning
confidence: 99%
“…CNS arteritis has been mentioned above. Retinal vasculitis is a severe, but rare complication of HZO treated by antiviral medication [62].…”
Section: Vasculitismentioning
confidence: 99%
“…Other authors proposed that retinal vasculitis may be involved in retinal vein occlusion. Sarpangala S et al reported a case of CRVO possibly secondary to retinal vasculitis [ 49 ]. Vasculitis following immunisation has been observed for other types of vaccines [ 50 , 51 ], although the causal link is unclear [ 51 ].…”
Section: Proposed Mechanisms Of Suspected Vaccine-related Rvomentioning
confidence: 99%
“… [1] Its typical clinical manifestation is sudden painless monocular vision loss. [2] In 1878, von Michel believed that the cause of the disease was venous embolism. At present, CRVO has become one of the main causes of blindness, [3] which negatively affects the quality of life, increases the psychological burden and financial burden.…”
Section: Introductionmentioning
confidence: 99%
“…Central retinal vein occlusion (CRVO), also known as retinal apoplexy, is one of the common clinical retinal vascular diseases [1] . Its typical clinical manifestation is sudden painless monocular vision loss [2] . In 1878, von Michel believed that the cause of the disease was venous embolism.…”
Section: Introductionmentioning
confidence: 99%